Infiltrative lipoma compressing the spinal cord in 2 large-breed dogs - Hobert, Marc K. (Canadian Veterinary Medical Association, 2013)
Two cases of infiltrative lipomas compressing the spinal cord and causing nonambulatory paraparesis in 2 large-breed dogs are reported. Magnetic resonance imaging (MRI) revealed severe extradural spinal cord compression by inhomogenous masses that infiltrated the adjacent tissues and the muscles of the spine in both dogs. The presumptive clinical diagnoses were infiltrative lipomas, which were confirmed by histopathology. In rare cases infiltrative lipomas are able to compress the spinal cord by the agressive growth of invasive adipocytes causing neurological deficits.